2013
DOI: 10.1016/j.biochi.2013.06.028
|View full text |Cite|
|
Sign up to set email alerts
|

Unveiling the effects of the secretome of mesenchymal progenitors from the umbilical cord in different neuronal cell populations

Abstract: It has been previously shown that the secretome of Human Umbilical Cord Perivascular Cells (HUCPVCs), known for their mesenchymal like stem cell character, is able to increase the metabolic viability and hippocampal neuronal cell densities. However, due to the different micro-environments of the distinct brain regions it is important to study if neurons isolated from different regions have similar, or opposite, reactions when in the presence HUCPVCs secretome (in the form of conditioned media-CM). In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…As it can be observed, BMSCs CM 24 h as well as HUCPVCs CM 24 h and 96 h had very similar results to those of the RA-differentiated cells group ( P > 0.05) (Figure 4 and Figures 5(a) to 5(c) and 5(e)), which is a strong indicator of the differentiation effects of the secretome of both BMSCs and HUCPVCs. Finally, the decrease in the mean neurite length observed in the BMSCs CM 96 h group ( P < 0.05) (Figure 4 and Figures 5(a) and 5(d)) may be related with the half-life of neurotrophic factors present in the CM at the point of their collection [19, 36, 37]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As it can be observed, BMSCs CM 24 h as well as HUCPVCs CM 24 h and 96 h had very similar results to those of the RA-differentiated cells group ( P > 0.05) (Figure 4 and Figures 5(a) to 5(c) and 5(e)), which is a strong indicator of the differentiation effects of the secretome of both BMSCs and HUCPVCs. Finally, the decrease in the mean neurite length observed in the BMSCs CM 96 h group ( P < 0.05) (Figure 4 and Figures 5(a) and 5(d)) may be related with the half-life of neurotrophic factors present in the CM at the point of their collection [19, 36, 37]. …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, SH-SY5Y cells differentiated with HUCPVCs CM 96 h exhibited significant greater expression of both DRD2 and DAT genes than cells differentiated with BMSCs CM 96 h ( P < 0.05, P < 0.01). The later result suggests not only that the different secretome composition of different tissue derived MSCs induces SH-SY5Y cells differentiation into different neuronal phenotypes but also that the effects mediated by the secretome of MSCs in neuronal differentiation are associated with the temporal profile of CM collection [19, 36, 37]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, both adipose stem cells (ASCs) and human umbilical cord perivascular cells (HUCPVCs) CMs were shown to increase hippocampal neurons survival and metabolic activity [73]. More recently, the secretome of HUCPVCs was also found to increase cell viability, proliferation, and neuronal cell densities in both cortical and cerebellar neuronal cultures [74]. Other in vitro and in vivo studies showed similar results [7577].…”
Section: Cell-based Therapies For Sci Repairmentioning
confidence: 88%